WORD FORMATION PROCESSES OF FASHION TERMS LISTED IN UK VOGUE'S WEBSITE - Hayuwardhani, Aurelia Reza (Lire Journal (Journal of Linguistics and Literature), 2019)
This paper aims to see the word formation processes in the fashion terms proposed by UK Vogue’s website. There are twenty six terminologies listed from A to Z. The terminologies became the data of the analysis in this paper. Each of the terminology was paid attention closely to identify the processes in the termilogies. The results show that fashion terms that are specifically listed on UK Vogue’s website implement five kinds of processes: 1) eponym, 2) borrowing, 3) compunding, 4) affixation, and 5) multiple processes or combination of previously mentioned processes. Out of those processes, borrowing processes are commonly used in forming fashion terms. Thus, it can be inferred that the formation of fashion terms are linked to the language that contributes more words in the fashion terminology vocabulary.